2020
DOI: 10.3389/fpsyg.2020.559779
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Emotional Responses to Functional and Hedonic Products: A Neuroscience Research

Abstract: Over the years, researchers have enriched the postulation that hedonic products generate deeper emotional reactions and feelings in the consumer than functional products. However, recent research empirically proves that hedonic products are more affect-rich only for some consumer segments or for specific consumption contexts. We argue that such inconsistency may derive from the nature of the emotions assessed that is strictly dependent on their empirical measurement and not from the mere existence of emotions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 90 publications
1
27
0
Order By: Relevance
“…Furthermore, neuroscience research has shown that the type of product, in terms of utilitarian or hedonic, also affects consumers' emotional responses (Bettiga et al, 2020). Since neuroimaging tools help to predict consumer behavior (Smidts et al, 2014;Cascio et al, 2015;Telpaz et al, 2015;Casado-Aranda et al, 2018a,b, 2020Motoki et al, 2020;Jai et al, 2021), future lines of research should consider which environmental factors (such as types of products, types of purchase, etc.)…”
Section: Emotional Contagion In Neurological Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, neuroscience research has shown that the type of product, in terms of utilitarian or hedonic, also affects consumers' emotional responses (Bettiga et al, 2020). Since neuroimaging tools help to predict consumer behavior (Smidts et al, 2014;Cascio et al, 2015;Telpaz et al, 2015;Casado-Aranda et al, 2018a,b, 2020Motoki et al, 2020;Jai et al, 2021), future lines of research should consider which environmental factors (such as types of products, types of purchase, etc.)…”
Section: Emotional Contagion In Neurological Reactionsmentioning
confidence: 99%
“…Marketing research on emotional contagion has focused on understanding how positive or negative emotions converge in positive or negative consumer behavior (Hennig-Thurau et al, 2006;Dellarocas et al, 2007;Cowley, 2014;Kramer et al, 2014;Fox et al, 2018). However, while marketing and psychology studies usually employ selfreported techniques to understand consumer behavior, the study of emotional contagion is quite suited to drawing on neurophysiological techniques to explain how emotions trigger mind and body arousal (Bell et al, 2018;Verhulst et al, 2019;Bettiga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroscience research has been employed widely in design fields to understand the responses of consumers, and physiological measures have been used to assess the experiences of consumers with new products (Bettiga et al, 2020 ). Consumer neuroscience can be utilized especially to link consumer choice and decision-making to marketing research (Camerer et al, 2004 ; Pirouz, 2007 ; Plassmann et al, 2012 ; Khushaba et al, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The general assumption is that biosensing data can provide marketers with information that cannot be obtained from conventional marketing methods (Khushaba et al, 2013 ). Further, research has shown that physiological data describing the emotional responses of consumers to functional products are disassociated from self-reported data (Bettiga et al, 2020 ). Because of the limited technological and analytical capacity, few studies have attempted to empirically analyze how consumer emotion is captured and how they respond to marketing stimuli (Huddleston et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation